Length based data of Nemipterus japonicus to spawning potential ratio (SPR) estimation on small scale fisheries (SSF) management in Sunda Strait. Issue 1 (February 2021) - Yonvitner,; Boer, M; Kurnia, R
Abstract: Spawning potential ratio (SPR) is an important parameter to ensure fish stock reproduction, recruitment, and sustainability. This approach more efficient and effective applied to poor and limited information and data to management. Therefore, we used the SPR approach in small scale fisheries, particularly on Nemipterus japonicus species in Labuan-Sunda Strait area. This research was conducted in the Labuan fish landing port from 2013 until 2019. The length data were collected each year and then analyzed using the basefoot ecologist toolbox application. The result has shown that SPR of N japonicus ranged from 1 to 6%, and it's relatively low and potentially unsustainable. Fish length spawning at 50 percent (SL50) ranged from 139 mm to 196.29 mm. And then fish length spawning at 95% (SL95) from 160.39 to 243.54 mm). Furthermore, in 2013-2018 monitoring activity SPR relatively low and decrease every year, and first at breeding (50% and 95%) also decrease. It means the gonad maturity and SPR could be used as an indicator of fishing pressure and sustainability.